2013
DOI: 10.1161/atvbaha.112.301001
|View full text |Cite|
|
Sign up to set email alerts
|

Rictor in Perivascular Adipose Tissue Controls Vascular Function by Regulating Inflammatory Molecule Expression

Abstract: Objective— Perivascular adipose tissue (PVAT) wraps blood vessels and modulates vasoreactivity by secretion of vasoactive molecules. Mammalian target of rapamycin complex 2 (mTORC2) has been shown to control inflammation and is expressed in adipose tissue. In this study, we investigated whether adipose-specific deletion of rictor and thereby inactivation of mTORC2 in PVAT may modulate vascular function by increasing inflammation in PVAT. Approach and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 52 publications
2
33
0
Order By: Relevance
“…23 Moreover, a high fat diet alone was sufficient to induce downregulation of rictor gene expression in PVAT and epididymal adipose depots. 23 These studies suggest that controlling mTORC2 activity in perivascular adipose tissues may offer a therapeutic avenue for inflammation-driven cardiovascular damage frequently observed in obesity.…”
Section: Perivascular Control Of Arterial Physiologymentioning
confidence: 97%
See 2 more Smart Citations
“…23 Moreover, a high fat diet alone was sufficient to induce downregulation of rictor gene expression in PVAT and epididymal adipose depots. 23 These studies suggest that controlling mTORC2 activity in perivascular adipose tissues may offer a therapeutic avenue for inflammation-driven cardiovascular damage frequently observed in obesity.…”
Section: Perivascular Control Of Arterial Physiologymentioning
confidence: 97%
“…Mammalian target of rapamycin complex 2 (mTORC2) is reported to control inflammation and is expressed in PVAT. 23 When rictor, an essential mTORC2 component, was deleted in mouse adipose tissue, gene expression and protein release of IL6, MIP-1α, and TNFα, were increased and dilations of aortic rings were impaired. 23 Moreover, a high fat diet alone was sufficient to induce downregulation of rictor gene expression in PVAT and epididymal adipose depots.…”
Section: Perivascular Control Of Arterial Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian target of rapamycin complex 2 has been shown to control inflammation and is expressed in adipose tissue. Bhattacharya et al 32 identified mammalian target of rapamycin complex 2 as a critical regulator of perivascular adipose tissue-directed protection of normal vascular tone. They concluded that modulation of mammalian target of rapamycin complex 2 activity in adipose tissue is a potential therapeutic approach for inflammationrelated vascular damage.…”
Section: Adventitial Tissues and Inflammatory Cells For Vascular Funcmentioning
confidence: 99%
“…They concluded that modulation of mammalian target of rapamycin complex 2 activity in adipose tissue is a potential therapeutic approach for inflammationrelated vascular damage. 32 …”
Section: Adventitial Tissues and Inflammatory Cells For Vascular Funcmentioning
confidence: 99%